2020
DOI: 10.1021/acs.accounts.0c00427
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Ring-Opening Metathesis Polymerization: From Concept to Creation

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Ring-opening metathesis polymerization (ROMP), which is derived from transition-metal-based olefin metathesis, has evolved into one of the most prevalent technologies for making functional polymeric materials in academia and in industry. The initial discovery of and advances in ROMP used ill-defined mixtures of metal salts to initiate polymerization.The initiators most commonly used today, developed with tremendous efforts, are well-defined metal−alkylidene com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Thus, there has been an interest in the discovery of nonmetal alternatives for ROMP. [30] Most notable in this regard, Boydston developed an elegant photoredox-mediated ROMP that utilized vinyl ethers as the propagating functionality. [31,32] Despite the highly creative and useful nature of this chemistry, issues of generality and scalability present challenges for its wider adoption.…”
Section: Ring-opening Metathesis Polymerization (Romp) Is Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there has been an interest in the discovery of nonmetal alternatives for ROMP. [30] Most notable in this regard, Boydston developed an elegant photoredox-mediated ROMP that utilized vinyl ethers as the propagating functionality. [31,32] Despite the highly creative and useful nature of this chemistry, issues of generality and scalability present challenges for its wider adoption.…”
Section: Ring-opening Metathesis Polymerization (Romp) Is Usedmentioning
confidence: 99%
“…In addition, certain applications such as those involving biomedical devices or electronics are incompatible with polymeric materials that contain metal impurities. Thus, there has been an interest in the discovery of non‐metal alternatives for ROMP [30] . Most notable in this regard, Boydston developed an elegant photoredox‐mediated ROMP that utilized vinyl ethers as the propagating functionality [31, 32] .…”
Section: Figurementioning
confidence: 99%
“…Therefore, while ROMP remains the most viable method to unlock the potential of BBCPs as large-area colorants (e.g., automotive paint), alternative backbones and polymerization methods are urgently required that can maintain efficient polymerization at high DPs while achieving a lower production cost. Potential alternative polymerization methods that could be applied towards the effective and inexpensive polymerization of BBCPs include metal-free ROMP, [40] grafting-onto click chemistry, [41] and orthogonal cationic and radical RAFT polymerizations. [42] Finally, recent examples employing supramolecular comb-like BCPs suggest an alternate strategy that bypasses these synthetic challenges, while also offering a degree of tunability via the formulation.…”
Section: Linear Block-copolymer (Lbcp)mentioning
confidence: 99%
“…[16][17][18][19][20][21] As a result of these innovations, photoinduced electron transfer (PET) has become a key feature of metal-free reversible deactivation radical polymerizations. [22][23][24][25][26] In 2017, Huang et al demonstrated O-ATRP using thermally activated delayed fluorescence (TADF) emitters as photocatalysts. 27 TADF is widely deployed in fields ranging from organic electronics, 28 photocatalysis, 29 biological imaging, 30 and chemical sensing 31,32 due to a unique ability to interconvert singlet and triplet excited states.…”
Section: Introductionmentioning
confidence: 99%